Pedagogical translanguaging in English classrooms: Teachers’ and students’ experiences in a Thai secondary school - Apiwit Pawapootanon; Somkiet Poopatwiboon; Eric A. Ambele (Australian Journal of Applied Linguistics, 2025)
This qualitative study examines how Thai EFL teachers utilize pedagogical translanguaging in multilingual secondary school classrooms, employing both planned and unplanned strategies to support English language learning. Grounded in Cenoz and Gorter’s (2021) multilingual pedagogical translanguaging model, the study investigates how teachers integrate students’ first languages (L1)—including Standard Thai and Isan—alongside English to scaffold comprehension, foster participation, and manage classroom interaction. Data were collected through classroom observations, video recordings, field notes, and stimulated recall interviews with three teachers and twelve students from three grade levels. Thematic analysis revealed five primary instructional functions of translanguaging: promoting engagement, enhancing understanding, boosting learner confidence, supporting mixed-ability groups, and facilitating classroom management. Students generally responded positively, citing increased clarity and reduced anxiety; however, some higher-proficiency learners preferred immersion approaches. The findings highlight the pedagogical value of translanguaging in EFL contexts, while also pointing to the challenges posed by prevailing English-only ideologies. The study advocates for more inclusive language education policies, enhanced teacher preparation in multilingual pedagogies, and ongoing research on learner experiences across diverse sociolinguistic contexts.